E USE OF OUTDOOR GAMES IN THE DEVELOPMENT OF PHYSICAL AND TECHNICAL FITNESS OF YOUNG HANDBALL PLAYERS - TULAGANOV , Shuxrat («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
is article examines the importance of outdoor games in the development of physical and technical fitness of young handball players. It has been proven that the use of outdoor games and specialized relay exercises to develop the physical and technical fitness of young handball players ensured their effective results and generated great interest in training sessions among adolescents.